2022 UK heatwave impacts on agrifood: implications for a climate-resilient food system - Davie, Jemma C. S.; Falloon, Pete D.; Pain, Daniel L. A.; Sharp, Tierney J.; Housden, Maddie; Warne, Thomas C.; Loosley, Tom; Grant, Erin; Swan, Jess; Spincer, James D. G.; Crocker, Tom; Cottrell, Andrew; et al. (Frontiers in Environmental Science, 2023)
Record-breaking high temperatures were experienced across the UK during summer 2022. The impacts of these extreme climatic conditions were felt across the food system, including increased energy costs for cold storage, the failure of refrigeration systems in numerous retail facilities, and impacts on livestock including heat stress. Future climate projections indicate an increased likelihood and duration of extreme high temperatures like those experienced in 2022. Learning from the impacts of the 2022 heatwave on the UK food system can help identify adaptations that build resilience to climate change. We explore the impacts through two case studies (UK poultry and wheat sectors), discuss potential adaptation options required for a climate-resilient, net-zero UK food system and consider future research needs.UK chicken meat production was 9% lower in July 2022 than July 2021; in contrast, energy costs increased for both production and refrigeration. Potential heatwave adaptation measures for poultry include transitioning to heat tolerant chicken breeds, lower stocking density, dehumidification cooling and misting systems, nutritional supplements, and improving retail refrigeration resilience and efficiency. UK wheat yields were 8% higher in 2022 than the 2017-2021 average. Increases were observed in every UK region but were least in the South and East where the heatwave intensity was strongest.2 This is a provisional file, not the final typeset article Future adaptation measures to avoid negative impacts of summer heat stress on winter wheat could include earlier maturing and heat/drought tolerant varieties, earlier autumn sowing, targeted irrigation for drought around anthesis, and soil and water conservation measures.